Pengaruh Kualitas Produk Dan Brand Image Terhadap Loyalitas Pelanggan Frisian Flag Di Muara Teweh - Sofia, Sofia (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2020)
This study aims to determine whether there is an effect of product quality on customer loyalty Frisian Flag. To find out if there is an influence of brand image on Frisian Flag customer loyalty. To determine whether there are influence product quality and brand image simultaneously on customer loyalty Frisian Flag. Metode collecting data used in this study were questionnaires and interviews. This research was tested with multiple Linear Regression. The population in this study are customers who are supplied by PT. Frisian Flag in Muara Teweh City area with 166 customers with sample criteria that is already a regular customer. The sample in this study amounted to 118 customers in Muara Teweh City and sold products from PT. Frisian Flag. There is a significant influence between product quality partially on Frisian Flag customer loyalty thus to increase customer loyalty the company management must maintain and improve the quality of its products. There is a significant influence between brand image partially on Frisian Flag customer loyalty. There is a significant influence between product quality and brand image simultaneously on customer loyalty Frisian Flag. The next researcher is expected to be able to examine with other variables beyond this studied variable to obtain more varied results. The company must be able to maintain or even improve product quality by designing attractive forms of packaging, products have good performance, more and more. fulfill these expectations as well the company can monitor the stock of Frisian Flag products in stores so that the stock of Frisian Flag products is maintained.